2019
DOI: 10.11646/zootaxa.4585.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal ciliates (Alveolata, Ciliophora) in Brazilian domestic horses (Equus caballus L.) and a review on the ciliate communities associated with horses around the world

Abstract: The aims of this study were to identify and quantify the gastrointestinal ciliates from Brazilian domestic horses, to compare the data obtained with previous studies and to review data on ciliate communities associated with horses around the world. We used eight domestic horses, kept under extensive management. Fecal samples were obtained immediately after defecation of animals and fixed in 18.5% formaldehyde. We identify 24 species of endosymbiotic ciliates, distributed in two subclasses, two orders, five fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Ciliates are the second most commonly encountered group of protists in our study in terms of findings and infected hosts; however, they are usually not reported except in specific studies. There is a great diversity of ciliates described in Artiodactyla, Perissodactyla, and Proboscidea, mostly corresponding to species of the orders Entodiniomorphida and Vestibuliferida [79][80][81][82][83][84]. Since the identification of different genera and species requires specific staining methods, and most of these species are considered commensal/endosymbionts, we made a generic identification of the findings in the hippopotamus, equids, rhinoceroses, and elephants as "endosymbiotic ciliates".…”
Section: Mammalian Hostsmentioning
confidence: 99%
“…Ciliates are the second most commonly encountered group of protists in our study in terms of findings and infected hosts; however, they are usually not reported except in specific studies. There is a great diversity of ciliates described in Artiodactyla, Perissodactyla, and Proboscidea, mostly corresponding to species of the orders Entodiniomorphida and Vestibuliferida [79][80][81][82][83][84]. Since the identification of different genera and species requires specific staining methods, and most of these species are considered commensal/endosymbionts, we made a generic identification of the findings in the hippopotamus, equids, rhinoceroses, and elephants as "endosymbiotic ciliates".…”
Section: Mammalian Hostsmentioning
confidence: 99%